The DC1-domain protein VACUOLELESS GAMETOPHYTES is essential for development of female and male gametophytes in Arabidopsis - D'ippólito, Sebastián (2017)
In this work we identified VACUOLELESS GAMETOPHYTES (VLG) as a DC1 domain-containing protein present in the endomembrane system and essential for development of both female and male gametophytes. VLG was originally annotated as a gene coding for a protein of unknown function containing DC1 domains. DC1 domains are cysteine- and histidine-rich zinc finger domains found exclusively in the plant kingdom that have been named on the basis of similarity with the C1 domain present in protein kinase C (PKC). In Arabidopsis, both male and female gametophytes are characterized by the formation of a large vacuole early in development; this is absent in vlg mutant plants. As a consequence, development is arrested in embryo sacs and pollen grains at the first mitotic division. VLG is specifically located in multivesicular bodies or pre-vacuolar compartments, and our results suggest that vesicular fusion is affected in the mutants, disrupting vacuole formation. Supporting this idea, AtPVA12 – a member of the SNARE vesicle-associated protein family and previously related to a sterol-binding protein, was identified as a VLG interactor. A role for VLG is proposed mediating vesicular fusion in plants as part of the sterol trafficking machinery required for vacuole biogenesis in plants.